The Evolution of Writing in the Science of Counting and Methodologies adopted by its Authors (Islamic Sciences Journal, 2023)
Objectives:1-         Demonstrate the evolution of writing in the Science of Counting Verses2-         trace the literature in verse counting, and classification of each book into its relevant phase.3-         Classifying writing phases, in terms of time span and content.Methodology:The methodology adopted is inductive, analytical, and historical methods.Main Results:1-         The books of the science of counting verses gradually added verse counters, ultimately mentioning them all.2-         The demonstration of oldest books within this science, showing the historic order and degree of inclusiveness of all topics part of the Science of Counting3-         The importance of only writing on the history of sciences following the examination of diverse writings within a science, in terms of time and methodology.Recommendations:-           To highlight a need to reassess the critical reproduction of some books on verse counting, in consideration to the impulsiveness of some authors during reproduction.-           To attract much attention to this science, especially among Quran reciters.